2018
DOI: 10.7774/cevr.2018.7.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of inactivated variant porcine epidemic diarrhea virus vaccines in growing pigs

Abstract: PurposeThe first aim of this study was to develop a novel inactivated porcine epidemic diarrhea virus (PEDV) vaccine using the recently isolated Korean PEDV QIAP1401 strain and to evaluate its protective efficacy in growing pigs. The second was to determine the optimum adjuvant formulation of the inactivated PEDV vaccine that induces protection against viral challenge.Materials and MethodsTo generate high titers of infectious PEDV, the QIAP1401 isolate was passaged in Vero cells. The experimental vaccines were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…The stimulation of mucosal immunity by trafficking antigen secreting cells (ASCs) to mucosa-related locations has been considered difficult via IM administration of vaccinations. However, IM administration is the most popular and convenient route for vaccinations in pig herds [6,[15][16][17]36,37]. In the present study, we have demonstrated that IM co-administration of iPEDV with CC chemokines as adjuvants could induce superior systemic antigen-specific IgG, mucosal antigen-specific IgA, and recruitment of CCR9+ and/or CCR10+ inflammatory cells at the injection site of the experimental pigs as compared to control piglets.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The stimulation of mucosal immunity by trafficking antigen secreting cells (ASCs) to mucosa-related locations has been considered difficult via IM administration of vaccinations. However, IM administration is the most popular and convenient route for vaccinations in pig herds [6,[15][16][17]36,37]. In the present study, we have demonstrated that IM co-administration of iPEDV with CC chemokines as adjuvants could induce superior systemic antigen-specific IgG, mucosal antigen-specific IgA, and recruitment of CCR9+ and/or CCR10+ inflammatory cells at the injection site of the experimental pigs as compared to control piglets.…”
Section: Discussionsupporting
confidence: 51%
“…Many attempts have been made to develop a safe and protective vaccine for controlling PED [4][5][6][7][8][9][10]. However, similar to studies on most enterotropic and mucosal transmissible viral diseases [11][12][13][14], using intramuscular (IM) administration of inactive or subunit vaccines combined with commercial adjuvants, such as multiple emulsions of water/oil/water or a B subunit of Escherichia coli heat-labile enterotoxin (LTB) induced production of systemic IgG and neutralizing antibodies but failed to elicit a mucosal IgA response and efficient protection [6,7,[15][16][17]. Furthermore, poor efficacies of currently commercialized vaccines have been reported [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies using full-length ectodomain trimeric S protein [ 40 ] or different truncated S proteins derived from different G2b PEDVs were combined with commercial adjuvants as subunit vaccine regimens. Despite that these subunit vaccines were able to induce robust systemic IgG and neutralizing antibody against PEDVs, they fail to completely prevent clinical symptoms and fecal viral shedding [ 47 , 48 , 49 ]. In the present study, piglets vaccinated with S-Bac can be elicited higher neutralizing antibody titers and good protective efficacy over the S1-Bac vaccinated pigs, despite both of them promoting robust levels of systemic PEDV S-specific IgG in pigs and mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, pregnant sows usually cannot be used in vaccination experiments because of breeding conditions and because experiment numbers and experimental expenditure are limited. Therefore, in this study, we used piglets to evaluate the protective efficacy of our experimental inactivated vaccine because pigs of all ages are susceptible to PEDV infection (Lee et al, 2018). The detection of serum antibodies showed that the experimental inactivated vaccine induced significant PEDV-specific serum IgG and neutralizing antibody responses to PEDV compared with mock control at 7, 14 and 21 dpv (P < 0.05, Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to molecular evidence, antigenic variations between classical and emerging highly virulent (non-S INDEL) PEDV strains were demonstrated in several serological cross reactivity assays (Kim et al, 2015;Lin et al, 2015aLin et al, , 2015bWang et al, 2015). There are also some studies showed that the highly virulent (non-S INDEL) PEDV strains could provide piglets against homologous challenge (Baek et al, 2016;Lee et al, 2018;Lin et al, 2016b ;Park et al, 2018). Therefore, there is an urgent need for more research aimed at understanding the biological characteristics, pathogenicity, and immune protective effects of the field prevalent strain in the GII genogroup.…”
Section: Discussionmentioning
confidence: 99%